Communication An Introduction - Rosengren, Karl Erik; Rosengren, Karl Erik (SAGE Publications, 1999)
Written as an introduction for beginning students, this book offers a thorough, yet lively, overview of human communication in all its aspects. Accessibly written and assuming no prior knowledge of the discipline Communication: An Introduction: offers a thorough, yet lively, examination of all aspects of human communication, including: a summary of its nature, form and function; a detailed analysis of all the levels of communication; a description and overview of the different traditions of communication studies; and a consideration of the future of communication - as a phenomenon and as a field of research.